Pengaruh Persepsi Mahasiswa terhadap Akuntabilitas Keuangan: Peran Mediasi Pemahaman Standar Akuntansi Pemerintahan (SAP) - Putri Syuhada; Raya Puspita Sari Hasibuan; Nuraini Nuraini; Eli Safrida (Jurnal Riset Akuntansi Politala, 2026)
This study examines the relationship among students' perceptions, their understanding of the Government Accounting Standards (SAP), and financial accountability in public-sector accounting education. It addresses the limited integration of conceptual mastery and accountable behavior. The analysis examines the influence of students' perceptions on financial accountability, with SAP understanding as a mediating variable. A quantitative explanatory research design was used. The study involved 184 students in the Public Financial Accounting program who had completed the government accounting course. Data were collected through questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to identify relationships among the variables. The results indicate that students' perceptions positively and significantly influence SAP understanding, but do not have a significant direct influence on financial accountability. However, SAP understanding significantly influences financial accountability and mediates the relationship between the variables. These findings suggest that when students' perceptions are accompanied by a solid understanding of SAP, this understanding serves as a cognitive foundation for financial accountability.